THE IMPORTANCE OF THE DUAL EDUCATION SYSTEM IN THE PROFESSIONAL TRAINING OF FUTURE TEACHERS (Universal International Scientific Journal, 2026)
The article provides information on the history, development and significance of the dual education system. The scientific works of foreign and Uzbek scientists who conducted scientific research in this area are analyzed. The importance of the dual education system in the training of teachers and the shortcomings in the formation of professional competence are discussed, and recommendations are made to eliminate these shortcomings through the dual education system. The importance of dual education in the training of future teachers is theoretically highlighted, and direct recommendations are developed. The dual education system studies the possibilities of training future teachers with theoretical knowledge and practical skills, developing professional competencies and ensuring flexible training in accordance with the requirements of the labor market. The article also extensively discusses the pedagogical approaches of the dual education system, training based on the competency model, the role of the practice and mentoring system in improving the qualifications of teachers. This is intended to develop scientifically based recommendations and contribute to improving the quality of training future teachers in the conditions of Uzbekistan.
Keywords: vocational education system; dual education; motivation